南极产碱性淀粉酶菌株NJ270的选育及酶学性质 - 杨帆; 徐宪忠; 赵晶; 曾润颖 (2012)
从南极中山站排污口沉积物样品中筛选到一株产碱性淀粉酶的耐冷菌株nJ270,结合形态学观察和16S rdnA序列分析表明该菌属于假单胞菌属(PSEudOMOnAS).发酵试验发现添加淀粉能使产酶量提高8.42倍.采用硫酸铵沉淀、Q SEPHArOSE Xl离子交换层析和SEPHAdEX g-75凝胶层析对假单胞菌nJ270淀粉酶进行了纯化,获得电泳纯的淀粉酶,SdS-PAgE检测结果表明该酶大小约为55 kdA.酶学性质研究表明其最适PH值为9.0,最适作用温度为50℃.在低于40℃的条件下具有较高的热稳定性,属于碱性中温淀粉酶.该酶可水解可溶性淀粉生成麦芽五糖.酶活力受多种金属离子和螯合剂的影响,其中Mg2+可使酶活力提高10%,而fE3+、CO2+、Cu2+、zn2+、Hg2+、EdTA则能抑制酶活性,抑制率均为60%左右.该酶的性质特征表明其在洗涤剂制造等工业生产中有一定的应用潜力. A psychro-tolerant bacteria NJ270 capable of producing alkaline amylase was isolated from the waste pipe of Zhongshan Station,Antarctica.It was identified as the genus Pseudomonas by its morphology and 16S rDNA sequence analysis.The production of amylase was increased by 8.42 times by adding starch during fermentation.Purification of Pseudomonas sp.NJ270 amylase was performed by ammonium sulfate precipitation,Q Sepharose XL anion-exchange chromatography and Sephadex G-75 exclusion chromatography in sequence.The result of SDS-PAGE electrophoresis indicated that the molecular weight of the enzyme was about 55 kDa.The optimum conditions for amylase activity were observed at pH 9.0 and 50℃.The amylase showed a better thermo-stability below 40℃.These results indicated that Pseudomonas sp.NJ270 was an alkaline mesothermal-active amylase.The enzyme hydrolyzed soluble starch into meltopentaose.The activity was stimulated by Mg2+ with an increment of 10%.However,it was inhibited by Fe3+,Co2+,Cu2+,Zn2+,Hg+and EDTA resulted in decrement of 60%.The characteristics of the enzyme show that it has a certain potential applications in detergent manufactures. 厦门海洋研究开发院资助项目;国家863计划资助项目(2007AA091407)